Tomb Site of The Kings of Gowa at The Tomb Complex of Sultan Hasanuddin - Nuraeni S,; Jusmiati, (Al-Hikmah, 2024)
In Gowa Regency there is a historical site as a material cultural heritage, namely the Grave Site of the Kings of Gowa which contains historical, cultural value and has meaning in the shape of the tomb. This tomb is located on Jalan Palantikang, Katangka Village, Somba Opu District, precisely on Tamalate Hill (Sultan Hasanuddin Tomb Complex). This research aims, firstly, to describe the history of the Tomb Site of the Kings of Gowa, secondly to describe the structure of the building form of the Tomb of the Kings of Gowa, and thirdly to describe the existence of the Tomb of the Kings of Gowa. Using types of field research with historical, archaeological, anthropological and religious approaches. Data collection methods are observation, interviews and documentation. Data processing and analysis techniques are data reduction, data presentation and conclusions. The results of this research are first, the tomb site is a relic of the Gowa Kingdom which once ruled South Sulawesi. Second, the structure of the Gowa Kings Tomb building consists of four types of tombs, namely, the stepped punde cupola tomb type, the dome cupola tomb type, the stone coffin tomb type, and the stone pile (earthen mound) tomb type. Third, the Gowa Kings' Grave Site still exists today and is used as a historical tourist attraction and has an influence in socio-cultural, educational and economic aspects. The novelty of this research is to describe a historical site in terms of history, the physical form of the tomb and the existence of the tomb site to date.